2019
DOI: 10.31545/intagr/108975
|View full text |Cite
|
Sign up to set email alerts
|

Development of new Lemnaceae breeding technology using Apol-humus and biogas plant waste

Abstract: Numerous possibilities of Lemnaceae use (biofuel production, supplementation of animal feed, phytoremediation, bioindication) as well as their cheap production and rapid growth offer many novel benefits. The experiment was carried out in laboratory conditions using Spirodela polyrrhiza plants. Plant cultivation was carried out in a phytotron room at 24°C, on the liquid standard "Z" medium which was supplemented with various concentrations of Apol-humus. Plant growth, chlorophyll index, net photosynthesis, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Alburquerque et al [ 11 ], Jasiulewicz and Janiszewska [ 12 ], and Łagocka et al [ 13 ] indicated that, given the environmental risks and benefits, the use of this waste in agriculture is most rational, provided that methods for its use are developed. The limitation of environmentally harmful synthetic fertilization by the use of biogas plant waste seems to be very important, as has been similarly demonstrated in the case of microalgae and water plants from the family Lemnaceae , which applied to medium enabled a reduction of the recommended artificial fertilizer doses [ 14 , 15 , 16 , 17 ]. The use of waste from biogas plants for fertilizing purposes is part of the strategy of the circulating production of energy plants in which waste becomes a raw material in the next crop cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Alburquerque et al [ 11 ], Jasiulewicz and Janiszewska [ 12 ], and Łagocka et al [ 13 ] indicated that, given the environmental risks and benefits, the use of this waste in agriculture is most rational, provided that methods for its use are developed. The limitation of environmentally harmful synthetic fertilization by the use of biogas plant waste seems to be very important, as has been similarly demonstrated in the case of microalgae and water plants from the family Lemnaceae , which applied to medium enabled a reduction of the recommended artificial fertilizer doses [ 14 , 15 , 16 , 17 ]. The use of waste from biogas plants for fertilizing purposes is part of the strategy of the circulating production of energy plants in which waste becomes a raw material in the next crop cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was conducted for 10 days under laboratory conditions on the model water plant S. polyrrhiza , derived from the collection of in vitro cultures of the Department of Plant Ecophysiology of the Faculty of Bioscience of the University of Lodz, Poland. Plant samples for testing were collected and evaluated according to methodologies developed on the basis of national standards and previous research, which are in force at University of Lodz in Poland and have been used in previous studies and international publication 19 . Test were conducted in accordance with OECD 221 Assess the toxicity of substances to freshwater aquatic plants of the genus Lemna (duckweed).…”
Section: Methodsmentioning
confidence: 99%
“…Lemnaceae are common monocotyledonous aquatic plants also called water duckweed, the most popular are: Spirodela , Landoltia , Lemna , Wolffiella and Wolffia 17 , 18 . These macrophytes are precursors of new generation crops, their cultivation is relatively easy and cost effective 18 , 19 . Fast growth and high accumulation of starch are two key features of the duckweed potential as a raw material for biofuel production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation